Breathing Exercise and Early Mobilization in Patients Post Aortic Valve Replacement with Ascending Aortic Aneurysm - Hanabilla Rawdhatul Jannah; Farid Rahman; Purnomo Gani Setiawan; Diani Qomaradewi Indah Sari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Postoperative respiratory distress and early decannulation are common complications following aortic valve replacement (AVR), particularly in patients with ascending aortic aneurysms. These conditions may delay recovery and increase the risk of adverse outcomes, highlighting the importance of early rehabilitation strategies. This case report aims to evaluate the effects of structured breathing exercises combined with progressive early mobilization during Phase I of cardiac rehabilitation in a postoperative AVR patient. A 61-year-old male patient admitted to the Cardiac Intensive Care Unit (CICU) underwent a structured intervention consisting of breathing exercises and progressive early mobilization. The program was conducted over three sessions, with monitoring of respiratory, hemodynamic, pain, and functional parameters. Following three intervention sessions, oxygen saturation improved from 94% to 100%, respiratory rate decreased from 27 to 20 breaths per minute, and pain intensity reduced from 4/10 to 0/10. Chest expansion increased by 0.5 cm at both axillary and xiphoid levels. Functional mobility, as measured by the ICU Mobility Scale, improved from 1 to 6. Hemodynamic parameters remained stable throughout the intervention, with no adverse cardiovascular events observed. In conclusion, structured breathing exercises combined with safe early mobilization appear to be effective in improving respiratory function, reducing pain, and accelerating functional recovery in high-risk patients following aortic valve replacement.Keywords: cardiac rehabilitation; breathing exercises; early mobilization; aortic valve replacement; ascending aortic aneurysm